Investigation of heavy metals mobility in shrimp aquaculture sludge-comparison of two sequential extraction procedures - Nemati, K.; Bakar, N.K.A.; Abas, M.R. (2009)
Influence of heavy metals was investigated by conducting various tests on the samples collected from aquaculture shrimp in Selangor, Malaysia. The concentration of heavy metals in the sludge and potential of mobility based on its association forms was studied. Two sequential extraction methods (five stages Tessier method and three steps BCR method) were used to determine the binding forms of the metals. From the analysis, Ca, Fe and Mn were found to be highest concentrated metals compared to Zn, Cu, Cr, Cd and Pb in aquaculture shrimp sludge. From the sequential extraction, Cd, Mn and Pb were mostly found in exchangeable/carbonate form, showed its susceptibility to be leached easily. Also Cu and Zn were extracted predominantly in oxidizable form. All metal concentrations (except Cd, Zn and Cu) were extracted to be higher in residual fraction in this method. The results of BCR method are totally similar to the five stages Tessier method. By comparing the percent of recovery, the BCR method was better than Tessier method. Nevertheless for both methods the percent of their recoveries were acceptable. For Pseudototal metal digestion, although the concentration of Cd is less than other heavy metals, it is very harmful as a fertilizer because Cd is one of the heavy metals that might be in the leaf or fruit of plants. Also for investigation of Ca in the sludge, this element was measured and high amounts of that show sludge is useful for growing of plant. The results of direct digestion of heavy metals show that with the control of Cd in this sludge we can use this sludge as fertilizer in soils for agriculture but it is better if it is used for fruitless plants.